Paleomagnetic Study of Selected Dykes and Lava Flows from Bandung Area - Edy Sunardi (Berita Sedimentologi, 1998)
Attempts have been made to determine the stability of a geomagnetic field for the last 4 Ma of Plio-Pleistocene volcanic rocks from the Bandung area, and it was found that the geomagnetic directions were indicated to be much deflected from the present geomagnetic direction, and in the present study were supported by complementary studies of petrographical and geochemical characteristics leads to a better comprehensive on the variations of the Earth's magnetic field. The result shown that most of K-Ar ages are consistent with obtained magnetic polarity and other stratigraphic indicators. Therefore, an improved chronostratigraphy in this area would be as a standard for correlation, especially to establish the Plio-Pleistocene stratigraphy on the area such like West Java in particular, which is mainly dominated by volcanic origin.